Innovative Plastering Mortars Based on Recycled Waste Glass. (2015) - Molnar, Luminita Monica; Manea, Daniela Lucia; Aciu, Claudiu; Jumate, Elena
Abstract: The aim of this study is to find a way to reuse the huge amounts of glass wastes in construction industry, by making new products at a lower price and also to reduce the glass wastes. In this research several types of ecological plastering mortars have been studied from a physical and mechanical point of view when natural aggregates were replaced by waste glass. The research also aims to study the impact which glass waste has on the hydration processes and the dimension of pores of the plastering mortars using innovative methods, such as optical microscopy and nuclear magnetic resonance. The objective of this study is to support the sustainable development policy, which requires mainly the development of eco-friendly constructions, based on two major goals: construction of buildings based on a sustainable design and constructions achieving energy performance.